Asuhan Keperawatan Gerontik Pada Pasien Dengan Rheumatoid Arthritis Di Panti Sosial Tresna Werdha Sabai Nan Aluih Sicincin Kabupaten Padang Pariaman - Cindhy Putri Utami; Hasmita Hasmita; Sandra Dewi; Armaita Armaita (CV. ITTC INDONESIA, 2026)
Rheumatoid Arthritis is a chronic disease that often occurs in the elderly and can cause pain, joint stiffness, and limitations in daily activities. This condition can reduce the quality of life of the elderly if not treated properly. This study aims to provide geriatric nursing care to rheumatoid arthritis patients at the Sabai Nan Aluih Sicincin Social Home for the Elderly in Padang Pariaman Regency. The method used is a case study with one client managed through the process of assessment, diagnosis determination, intervention, implementation, and evalu ation of nursing conducted from February 26 to March 3, 2026. The results of the study showed nursing diagnoses in the form of chronic pain, impaired physical mobility, and risk of falls. Interventions provided included pain management, mobilization support, and environmental safety management. After nursing actions for 5 days, the client's pain level decreased, physical mobility abilities increased, and the risk of falls could be minimized through the nursing interventions provided. It is hoped that the elderly can apply relaxation techniques, simple mobilization exercises, and maintain environmental safety to help reduce pain and prevent the risk of falls.